Hand-Schuller-Christian disease (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Hand-Schuller-Christian disease (HSC) is a rare disease of unknown cause. We report a case of Hand-Schuller-Christian disease with a solitary swelling over left parieto-occipital region of scalp, and increased thirst with polyuria. Prompt diagnosis and treatment of the disease will improve the life expectancy.